Coherence and transparency: some advice for qualitative researchers - Crispin Coombs (Production)
Abstract There is relatively little advice in the Engineering domain for undertaking qualitative studies. Researchers have to rely on generic guidance that may result in imprecise application of qualitative methods. A related discipline to Engineering is Information Systems (IS) and the experiences of the IS domain may provide some useful insights for undertaking qualitative studies. This paper synthesizes the guidance from the IS community for crafting high quality qualitative studies and manuscripts. It reports on five themes: i) Establishing philosophical underpinnings; ii) Clarifying theoretical aims; iii) Selecting qualitative methods; iv) Demonstrating rigour in qualitative data analysis; and v) Grappling with generalisation. The review stresses the importance of coherence and transparency for crafting qualitative research manuscripts and provides a list of reflective questions for qualitative research design.